ANALISIS PEMBELAJARAN BERBASIS PROJEK DALAM PEMBENTUKAN KARAKTER SISWA SD - Fransiska Priska Oliviani Ahoinnai; Karlah Liu; Pasriani Damayanti Akunut; Windi Astuti Hana Kore; Adam Bol Nifu Benu; Habibi Musa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine how the Project Based Learning (PBL) model is applied in shaping the character of fifth-grade st udents at GMIT Elementary School No. 7 Oebufu. The study used a descriptive quantitative approach with a case study design, and data were collected through observation, interviews, and documentation. Analysis was conducted by calculating scores and percentages for each character indicator, including responsibility, cooperation, discipline, creativity, honesty, and social awareness. The results showed that the implementation of PBL had a positive and significant impact on strengthening students' character. The percentage of achievement for all indicators was in the good to very good category, with an overall average of 92.08%. The cooperation indicator obtained the highest results, followed by creativity and discipline. Meanwhile, the responsibility, honesty, and social awareness indicators continued to show consistent development in the high category. This confirms that project-based learning is able to activate students in the learning process, encourage independence, and foster positive behavior through direct and collaborative activities. Thus, project-based learning can be used as an alternative, effective learning strategy for developing student character at the elementary school level.